A unified model of melatonin, 6‐sulfatoxymelatonin, and sleep dynamics. Issue 4 (8th March 2018) - Abeysuriya, Romesh G.; Lockley, Steven W.; Robinson, Peter A.; Postnova, Svetlana
Abstract: A biophysical model of the key aspects of melatonin synthesis and excretion has been developed, which is able to predict experimental dynamics of melatonin in plasma and saliva, and of its urinary metabolite 6‐sulfatoxymelatonin (aMT6s). This new model is coupled to an established model of arousal dynamics, which predicts sleep and circadian dynamics based on light exposure and times of wakefulness. The combined model thus predicts melatonin levels over the sleep‐wake/dark‐light cycle and enables prediction of melatonin‐based circadian phase markers, such as dim light melatonin onset (DLMO) and aMT6s acrophase under conditions of normal sleep and circadian misalignment. The model is calibrated and tested against group average data from 10 published experimental studies and is found to reproduce quantitatively the key dynamics of melatonin and aMT6s, including the timing of release and amplitude, as well as response to controlled lighting and shift work.